Test–Retest Reliability of the Balance Tracking System Modified Clinical Test of Sensory Integration and Balance Protocol Across Multiple Time Durations - Goble DJ (Dove Medical Press, 2021)
Daniel J Goble,1 Nathan O Conner,1 Michael R Nolff,1 Joshua L Haworth,1 Bradley J Kendall2 1Exercise Science Program, Department of Human Movement Science, Oakland University, Rochester, MI, 48309, USA; 2Department of Kinesiology, Taylor University, Upland, IN, 46989, USACorrespondence: Daniel J GobleExercise Science Program, Department of Human Movement Science, Oakland University, 433 Meadow Brook Road, Rochester, MI, 48309-4452, USATel +1 248 364-8688Fax +1 248 364-8657Email dgoble@oakland.eduBackground: Postural control is critical for body sway control and is subserved by three sources of sensory feedback (ie, vision, proprioception and vestibulation). A method for determining the relative contribution of each sensory feedback source to postural control is the modified clinical test of sensory integration and balance for the balance tracking system (BTrackS). However, this method has not yet been evaluated for test–retest reliability.Purpose: To determine the test–retest reliability of the modified clinical test of sensory integration and balance protocol for the BTrackS across multiple time intervals.Methods: Three groups of healthy young adults performed the BTrackS modified clinical test of sensory integration and balance protocol four times separated by either one day, one week or one month. Within each time duration group, and condition, differences in total center of pressure path length were determined from one test session to the next and intra class correlation coefficient categorizations were made.Results: In all but one case, no significant difference in performance was seen from one testing session to the next. The one significant difference found was a decrease in total center of pressure path length from day 1 to day 2 in the vestibular condition of the group tested daily. Intra class correlation coefficient results largely indicated fair-good reliability across time durations and test conditions.Conclusion: The present study largely supports use of the BTrackS modified clinical test of sensory integration and balance protocol as a means of probing the sensory contributions to balance performance across multiple time durations.Keywords: sensory feedback, postural control, reliability, balance assessment